Early detection of liver disease in patients with alcohol use disorder improves long-term abstinence. - Orgill, Amelia; Jew, Michael H; Soltani, Maryam; Deioma, Ann; Grant, Meghan; Patton, Heather M; Hsu, Cynthia L (Alcohol & Alcoholism, 2024)
Aims Excessive alcohol consumption is a major global health concern, contributing to millions of deaths annually and a significant proportion of cirrhosis cases; however, standardized protocols for early identification of alcohol-associated liver disease are lacking. In this retrospective cohort study, we aimed to understand the prevalence and risk factors associated with elevated liver stiffness measurement (LSM) in high-risk patients with alcohol use disorder (AUD) and identify variables associated with longitudinal abstinence and outcomes. Methods Veterans with severe AUD without known liver disease admitted to a 35-day residential substance use treatment program were offered liver health screening, including Fibroscan evaluation. Assessment of AUD severity and liver health outcomes were evaluated longitudinally by chart review. Results and Conclusions In a cohort of 257 veterans with severe AUD admitted to residential treatment, 185 underwent Fibroscan evaluation, and 22 were identified to have elevated LSM concerning for compensated advanced chronic liver disease. Patients with elevated LSM were more likely to remain abstinent after 1 year. About 41% of patients with LSM ≥ 10 kPa (5% of all screened patients) were confirmed to have cirrhosis on follow-up and incorporated into routine hepatology care. Screening of liver disease in high-risk populations with non-invasive imaging modalities provides an opportunity to identify patients at risk for compensated advanced chronic liver disease before decompensation. Identification of increased risk for advanced chronic liver disease may promote abstinence in patients with severe AUD. Collaboration between mental health professionals and hepatologists is critical for the integration of care for patients with AUD and liver disease.